PRIORITY STRATEGIES FOR ENHANCING THE EFFECTIVENESS OF EDUCATION AND TRAINING PROGRAMS IN TVRI PRODUCTION AND BROADCASTING - Sifak Sifak; Soewarto Hardhienata; Dian Wulandari (Yayasan Education and Social Center, 2026)
The rapid development of digital technology and the transformation of the broadcasting industry require TVRI to strengthen the quality and competitiveness of its human resources through effective education and training programs. This study aimed to formulate priority strategies for improving the effectiveness of education and training programs in production and broadcasting at TVRI using the Scientific Identification Theory to Conduct Operation Research in Education Management (SITOREM) approach. The study employed a quantitative descriptive method involving 164 employees selected through quota sampling from a population of 278 employees across 30 TVRI stations in Indonesia. Data were collected using questionnaires measuring training effectiveness, competency development effectiveness, transformational leadership, communication technology literacy, and information technology literacy. Data were analyzed using path analysis and SITOREM analysis. The results revealed that communication technology literacy had the strongest direct effect on training effectiveness (β = 0.472), followed by transformational leadership (β = 0.182), information technology literacy (β = 0.150), and competency development effectiveness (β = 0.137). SITOREM analysis identified fourteen indicators that require immediate improvement, namely communication, data management, evaluation, intellectual stimulation, inspirational motivation, individual consideration, technology integration in learning, creative technology application, knowledge development, performance improvement, work-experience implementation, leadership enhancement, training alumni empowerment, and training method development. These findings indicate that strengthening technological literacy, transformational leadership, competency development, and post-training utilization are strategic priorities for improving training effectiveness and supporting TVRI’s digital transformation.